Best Answer

4 times the square root of 5. it's undefinable so that's the most you can simplify it without using imaginary numbers

Q: What is 4 times the square root of 3 times 2?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

The square root of 12 equals the square root of 4 times 3. The square root of 4 is 2. The square root of 12 equals 2 times the square root of 3.

It is: (3*2)-(2*2) = 2

hmm... okay, if I understand you correctly, 2 times the square root of 3 times the square root of 12? = 2(1.73)(3.46) = 11.9716. If you aren't using the approximations, then just simplifying is... [sorry, I can't do the square root sign on the computer...] 2(square root of 3)(square root of 12) = 2(square root of 3)(square root of 4*3) = 4(square root of 3)(square root of 3) = 4(3) = 12!!! HOPE I HELPED!! :-)

8 times the square root of three or 13.85640646055101834821957073204697893554244203048304502...

square root of 4x is 2 times square root of x, so answer is square root of x times 3 since it is 2 square roots of x plus one of them

Related questions

square root 2 times square root 3 times square root 8

3(3 square root of 2) = 9(square root of 2)

if you take out the word ''quantity'' your answer is 25.02725024

2 times the Square root of 3 + 4

The square root of 12 equals the square root of 4 times 3. The square root of 4 is 2. The square root of 12 equals 2 times the square root of 3.

It is: (3*2)-(2*2) = 2

7.4915627415691541308549385962873

hmm... okay, if I understand you correctly, 2 times the square root of 3 times the square root of 12? = 2(1.73)(3.46) = 11.9716. If you aren't using the approximations, then just simplifying is... [sorry, I can't do the square root sign on the computer...] 2(square root of 3)(square root of 12) = 2(square root of 3)(square root of 4*3) = 4(square root of 3)(square root of 3) = 4(3) = 12!!! HOPE I HELPED!! :-)

It works out as -26 times the square root of 3

24

No because the square root of 98 is 7 times the square root of 2

(3 x 2) - (2 x 2) = 2